Anomaly detection methods in sample datasets when managing processes in systems by the state - Lykhach, Oleh; Ugryumov, Mykhaylo; Shevchenko, Dmytro; Shmatkov, Sergei (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2022)
The current information software does not allow solving the problems of detecting outliers in data samples and time series with a sufficiently high level of reliability.Therefore, this work is devoted to the choice of metrics for assessing the correctness of detecting outliers, as well as the best mathematical models and methods for solving the problem of detecting outliers in test samples when managing processes in systems by state. Mathematical models and methods for detecting outliers (anomalous values) and Python-based software tools such as scikit-learn, Tensorflow, NumPy, Pandas and others have been used. The results of our work are the overview of the metrics used to assess the effectiveness of mathematical models and methods for detecting outliers; the overview of traditional and deep learning techniques of detecting outliers; the results of researching the efficiency and quality of mathematical models and methods for detecting outliers using 12 datasets; the conclusions about the best metric and the best mathematical models and methods for solving the problem of detecting outliers in test samples when managing processes in systems by state.The selected methods are mainly used for monitoring the level of anomalous values in various datasets when managing processes in systems by state, which makes these methods universal.